Assessment of research faculty development program efficacy in writing research proposals - Gurat, Melanie G.; del Rosario, Fe Yolanda Gatan; Dizon, Pia Kristina Ligot; Saludarez, Marlon U. (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2018)
The dearth in research in Philippine higher education institutions (HEIs) had driven the Commission on Higher Education (CHED) to provide policies and mandates that are largely geared towards the improvement of research productivity. Saint Maryâs University responded through Faculty Research Development Program, a scheme borne of the plans of the University Research Center (IDP Year 2013-2014) that aims to strengthen and enhance the research skills of faculty members. This study aimed to assess the efficacy of the research faculty development program workshop in writing full-blown research proposals. It involved the quantitative type of research using the posttest-only control group experimental design since the subjects were evaluated after the intervention. Evaluative in nature, it was conducted at Saint Maryâs University, located at Bayombong, Nueva Vizcaya in Cagayan Valley. There were 25 subjects of the study who were all participants in the seminar-workshop. Researcher-made questionnaires and evaluated research proposals were the primary sources of the data in the study. Findings revealed that the research faculty development program workshop on writing research proposals was efficient. Hence, faculty members are highly recommended to continue participating in research capability training to become part of the tri-fold function of the university - the instruction, community extension, and research.